BRINGING TECHNOLOGY INTO THE CLASSROOM: STUDENTS’ EFFORT TO SHAPE PRONUNCIATION - Ramli Ramli; Vivit Rosmayanti; Andi Hamzah Fansury (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2023)
One of the essential skills in teaching English is pronunciation. The listener will only understand the speaker if their pronunciation is correct. Applying English pronunciation instructions to students is an integral part of the language. This study aimed to investigate the effectiveness of the podcast which contains relevant and authentic content for global listening comprehension in language learning. As a technological tool, the “British Council” podcast was integrated for learning English pronunciation at English Education in Universitas Borneo Tarakan. This pre-experimental study involved one class of third-semester students who previously learned pronunciation. Because the calculated Z value was less than the -Z table (-4.809 -1.960) and the p-value was less than (0.000 0.050), the decision was made to reject H0, indicating an average significant difference between the pre-test and post-test based on the measured pronunciation. It presented that integrating the podcast shaped students’ pronunciation and made them more confident. This study sheds light on the role of digital media in determining students' pronunciation and language development. It also provides teachers with alternative media for learning pronunciation in and outside of the classroom.